Penerapan Digital Marketing dan Promosi Pada Perusahaan PT. Penawar Legenda Maju - Fitri Maulida Husna; Nurbaiti, Nurbaiti (Universitas 45 Surabaya, 2024)
In the rapidly developing digital era, digital marketing and promotional strategies have become the core of companies' efforts to achieve success and sustainable business growth. PT Penawar Legenda Maju (PLM), a leading network marketing company in Indonesia, has utilized digital marketing to achieve its business goals. Superior products such as PLMSaipress Drops, MySaipress Capsules, MyAdam, AdamQu Coffee, and BioSaipress Soap have won the hearts of Indonesian consumers thanks to their guaranteed quality and safety. This research uses qualitative methods with a descriptive approach to investigate the digital marketing strategies used by PT. PLM JAYA and analyze the impact of implementing digital marketing on relationships with consumers, company performance and economic development. The research results show that PT. PLM JAYA has succeeded in applying information technology theory efficiently, increasing operational efficiency, interacting with customers via social media, and optimizing digital marketing strategies. Digital marketing and promotions have become a key element in a company's marketing strategy, increasing brand awareness, sales and interaction with customers. By focusing on a specific target market, interesting content, performance measurement, and clear promotional messages, PT. PLM JAYA has succeeded in expanding market reach and achieving success in digital marketing of their products and services. This research provides valuable insights into the integration of information technology in digital marketing and promotional strategies, with practical implications for companies in various sectors looking to achieve competitive advantage in an ever-changing market. Digital marketing and promotions have become the driving force for modern business growth, and PT. PLM JAYA has succeeded in taking full advantage of this potential.